Prevalence and determinants of antenatal depression and its association with intimate partner violence: a cross-sectional study at Hospital Melaka, Malaysia - Narayanan, Sethuckarasi; Abd Rahman, Fairuz Nazri; Sutan, Rosnah; Kumarasuriar, Gayathri K.; Leong, Andrew Kah Seong (Frontiers in Psychiatry, 2024)
ObjectiveThis study aimed to assess the determinants of antenatal depression and its relation to intimate partner violence (IPV) among pregnant women at Hospital Melaka, Malaysia.MethodsA cross-sectional study was conducted between February 1 and March 31, 2024, with 370 pregnant women recruited through convenience sampling. Inclusion criteria were Malaysian citizenship, age above 18 years, and ability to read and comprehend Malay. Data collection involved self-reported sociodemographic questionnaires, the Edinburgh Postnatal Depression Scale (EPDS), and the WHO Multicountry Study on Women’s Health and Life Events Questionnaire.ResultsThe prevalence of antenatal depression was 8.4%. IPV was reported by 64.1% of participants, with 54.6% experiencing controlling behavior, 30.0% emotional violence, 2.4% physical violence, and 3.5% sexual violence. Bivariate analysis showed that emotional violence (p < 0.001), physical violence (p < 0.001), sexual violence (p < 0.001), and hospitalization (p = 0.006) were significantly associated with an increased risk of antenatal depression. Multivariable logistic regression revealed that women receiving outpatient care had significantly lower odds of developing antenatal depression compared to hospitalized women (adjusted OR 0.262, 95% CI 0.100–0.683; p = 0.006). Women who experienced sexual violence were 18 times more likely to develop antenatal depression (adjusted OR 18.761, 95% CI 3.603–97.684; p < 0.001).ConclusionThe study highlights the need for healthcare workers to recognize risk factors for antenatal depression, particularly IPV.